Dual platelet antiaggregation therapy after myocardial revascularization surgery - Feitosa,Mateus Paiva Marques (2019)
SUMMARY Coronary artery bypass graft (CABG) is a consolidated treatment in patients with coronary artery disease (CAD) for both symptom control and improvement of prognosis. The patency of venous grafts is still the most vulnerable point of the surgical treatment since it presents a high prevalence of occlusion both in the immediate postoperative period and in the long-term follow-up. Aspirin plays a well-established role in this setting, and for a long time, clopidogrel use has been restricted to patients allergic to aspirin. Recently, subgroup analyses of studies with different anti-platelet therapies have shown reduced mortality and cardiovascular events in patients on dual anti-platelet antiplatelet therapy (DAPT) undergoing CABG, although such studies have not been designed to evaluate this patient profile. However, there is still an insufficient number of randomized studies using DAPT in this context, resulting in a disagreement between the European and American cardiology societies guidelines regarding their indication and generating doubts in clinical practice.